Evaluación de herbicidas de pre y postemergencia temprana en el cultivo de maíz (Zea mays) en el Cantón Vinces, Provincia de Los Ríos - YAUQUI PUNINA, EDGAR VINICIO (2023)
The present experimental work dealt with the evaluation of pre- and early post-emergence herbicides in corn cultivation, which was carried out on the lands of Mr. Edgar Vinicio Yauqui Punina, located in the Vinces Canton, Los Ríos province. The maize hybrid ADV 9789 was used as planting material. The herbicides Isoxaflutole +thiencarbozone (0.35 L/ha), Isoxaflutole (0.89 kg/ha), Thifensulfuron+ Nicusulfuron +atrazina (0.50 L/ha), Mesotrione (0. 30 L/ha), manual control and farmer control (Nicosulfuron) (25 g/ha). The conclusions determined that the weeds present in the corn crop in the Vinces area, Los Ríos province were Chloris virgata (Indian beard), Eleusine indica (Hicken's foot), Ischaemun rogusum (Wheat straw), Rottboellia cochinchinensis ( Caminadora), Cyperus rotundus (Coquito) and Ipomoea spp (Betilla)¸ post-emergence herbicides positively influenced maize, controlling certain types of weeds, and being considered selective for the crop; the best weed control occurred with the application of the herbicide Thifensulfuron+Nicusulfuron +atrazina at a dose of 0.50 L/ha, acting post-emergence and the applied herbicides did not cause toxicity in the corn crop, reporting little damage after 20 days and disappearing 40 days after the application of the product. The recommendations were to apply the herbicide Thifensulfuron+Nicusulfuron +atrazina at a dose of 0.50 L/ha in the early post-emergence crop of maize; replicate the research in other edapho-agroecological zones and promote the use of post-emergence herbicides in adequate doses to avoid weed resistance to the products.